2002
DOI: 10.1016/s1532-0456(02)00083-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of measured and modelled copper binding by natural organic matter in freshwaters

Abstract: Fifteen freshwater samples containing significant concentrations of dissolved organic carbon-[DOC]-were titrated with copper under standardised conditions (pH 6 and 7), and concentrations of Cu(2+)-[Cu(2+)]-were measured with an ion-selective electrode. Measured values of [Cu(2+)], which were in the range 10(-11)-10(-5) moll(-1), were compared with those simulated using Humic Ion-Binding Models V and VI. It was assumed that copper speciation was controlled by the organic matter, represented by fulvic acid (FA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 16 publications
7
128
1
3
Order By: Relevance
“…Especially, for DOC, it was demonstrated that it was a good predictor of acute Cu toxicity for D. magna and D. pulex and that it is one of the most important factors influencing Cu bioavailability. A number of studies have been carried out to investigate spatial and temporal variations of metal concentrations and the effects and interactions of specific water quality parameters on the toxicity and bioavailability specifically of copper (Gundersen and Steinnes, 2001;Park et al, 2009;Ryan et al, 2009;Bryan et al, 1999Bryan et al, , 2002. These earlier studies support the present results in terms of the identified relationships between water quality parameters and Cu speciation and bioavailability in the studied water environments.…”
Section: Seasonal Variation Of Acute Lc 50 Cu and Chronic Maximum Crisupporting
confidence: 85%
“…Especially, for DOC, it was demonstrated that it was a good predictor of acute Cu toxicity for D. magna and D. pulex and that it is one of the most important factors influencing Cu bioavailability. A number of studies have been carried out to investigate spatial and temporal variations of metal concentrations and the effects and interactions of specific water quality parameters on the toxicity and bioavailability specifically of copper (Gundersen and Steinnes, 2001;Park et al, 2009;Ryan et al, 2009;Bryan et al, 1999Bryan et al, , 2002. These earlier studies support the present results in terms of the identified relationships between water quality parameters and Cu speciation and bioavailability in the studied water environments.…”
Section: Seasonal Variation Of Acute Lc 50 Cu and Chronic Maximum Crisupporting
confidence: 85%
“…Examples include 71 the acidification of soils [7][8][9][10][11][12][13][14] and surface waters [15] , trace metal behaviour in soils [16][17][18][19][20][21][22] , surface 72 waters [23][24][25][26][27][28][29][30][31] and groundwaters [32] , lake sediment diagenesis [33,34] , rare earth geochemistry [35-73 37] , iron and manganese geochemistry [38][39][40][41] , radionclide geochemistry [42][43][44][45] , organic matter 74 solubility in soils [46,47] , catchment modelling [48,49] , interactions of metals with biota [50,51] , 75 ecotoxicology [52][53][54][55][56][57][58][59] and Critical Loads …”
Section: Tipping Et Al Humic Ion-binding Model Vii_revisionmentioning
confidence: 99%
“…[16] The binding activity of DOM was estimated by assuming DOM to be 50 % carbon, and that 65 % of the DOM behaves like isolated FA whereas the rest is inert. [36,37] For example, a DOC concentration of 5 mg L À1 corresponds to [DOM] of 10 mg L À1 , and so the concentration of FA for modelling is 6.5 mg L À1 . All the predictions reported here were made using only humic-type DOM, i.e.…”
Section: The Data Setmentioning
confidence: 99%